Sumatriptan activates TRPA1 - Alexandru Babes; Cristian Neacsu; Michael JM Fischer; Karl Messlinger (SAGE Publishing, 2019)
Background: Migraine therapy with sumatriptan may cause adverse side effects like pain at the injection site, muscle pain, and transient aggravation of headaches. In animal experiments, sumatriptan excited or sensitized slowly conducting meningeal afferents. We hypothesized that sumatriptan may activate transduction channels of the "irritant receptor," the transient receptor potential ankyrin type (TRPA1) expressed in nociceptive neurons. Methods: Calcium microfluorometry was performed in HEK293t cells transfected with human TRPA1 (hTRPA1) or a mutated channel (TRPA1-3C) and in dissociated trigeminal ganglion neurons. Membrane currents were recorded in the whole-cell patch clamp configuration. Results: Sumatriptan (10 and 400 µM) evoked calcium transients in hTRPA1-expressing HEK293t cells also activated by the TRPA1 agonist carvacrol (100 µM). In TRPA1-3C-expressing HEK293t cells, sumatriptan had hardly any effect. In rat trigeminal ganglion neurons, sumatriptan, carvacrol, and the transient receptor potential vanillod type 1 agonist capsaicin (1 µM) generated robust calcium signals. All sumatriptan-sensitive neurons (8% of the sample) were also activated by carvacrol (14%) and capsaicin (48%). In HEK293-hTRPA1 cells, sumatriptan (100 µM) evoked outwardly rectifying currents, which were almost completely inhibited by the TRPA1 antagonist HC-030031 (10 µM). Conclusion: Sumatriptan activates TRPA1 channels inducing calcium inflow and membrane currents. TRPA1-dependent activation of primary afferents may explain the painful side effects of sumatriptan.